(untitled) (Eurasian Journal of Ecology, 2016)
This article analyzes the status and use of major energy resources of the Republic of Kazakhstan. Also were described thermoelectric plants of republic. Objective in this research is Almaty CHP-1.Offered “green” technology for further injection with attraction of resource with potential power, but rare used brown coal. In technology that observed in this research was used gas generator, which based on “Lurgi” technology. Thus, this article contains the information about main characteristics of synthetic gas, which can be obtained in gas generator.